Factors Affecting Grafting Density in Surface‐Initiated ATRP: A Simulation Study. Issue 3 (2nd February 2016) - Mastan, Erlita; Xi, Li; Zhu, Shiping
Abstract : Various factors affecting grafting density in surface‐initiated atom transfer radical polymerization are investigated through simulation approach. It is found that the final grafting density decreased as more monomer is added between one activation and deactivation cycle due to shielding. The results can be used in conjunction with termination theory to explain the conflicting experiment trends reported in the literature. Abstract : In surface‐initiated atom transfer radical polymerization, knowledge of grafting density is of significant interest because it is one of the determining properties of grafted polymer. It is well known that not all of the immobilized initiators can grow into polymer chains. However, little is known about why this happens and what affects the grafting efficiency. The lack of information is partly due to the difficulty in experimental determination of grafting density on flat substrates. To circumvent the problem, Monte Carlo simulation with bond fluctuation model is used in this study to investigate the effects of various reaction conditions on the grafting density. The simulation results show lower grafting density when less deactivator is present. In systems with lower deactivator concentration, the number of monomer added per activation cycle is higher. Coupling this with close proximity of immobilized initiators results in chains initiated at earlier time to shield their neighboring initiator moieties from adding monomers, thus lowering the grafting density in such a system. These simulation results also provide an explanation to the seemingly conflicting trend reported in the literatures.